Gramática, cognição e sociedade: para uma gramática de significados, usos e variações - Soares da Silva, Augusto (Revista da Associação Portuguesa de Linguística, 2019)
This study aims to highlight the relationship between grammar, cognition and society, identifying cognitive and social processes applied to grammatical constructions in Portuguese and their correlations. First, we will characterize certain cognitive operations that play an important role in grammar and that make it an efficient conceptual structuring and communication system: construal (our ability to view, conceive and portray the same situation in alternate ways); objectivity vs. subjectivity (the construal of a scene as detached or not from the conceptualizer); prominence (the focusing of attention on some aspects of a situation); mental spaces (packages of encyclopedic knowledge built and evoked in the current discourse); and inferences about the speaker’s intended meanings. Then, we will show how these cognitive operations (which are common to language and other cognitive faculties, such as perception, attention, and memory) are configured and conditioned by sociocultural factors and communicative efficiency processes – hence the importance of intersubjectivity and cultural conceptualization, and the need for systematically including intralinguistic variation in grammar. The answer to the question of the correlation between cognitive processes and social processes in grammar is based on the cognitive science notion of social cognition and on multivariate and sociocognitive grammar models. A usage-based grammar implies a deconstruction of the linguistic system in favor of a view of language in its inevitable variability as a complex dynamic system and the construction of a multifactorial grammar model that may adequately unravel, through multivariate quantitative methods, the interplay between conceptual, structural and social factors. Finally, we will illustrate these principles of a grammar of meanings, uses and variations (in contrast with traditional perspective of a grammar of forms, structures and rules) with three studies on constructional variation in Portuguese. They are part of our sociocognitive and sociolectometrical research into convergence and divergence between European and Brazilian Portuguese: se constructions (reflexive, reciprocal, middle, anticausative, passive, impersonal) and the null se constructions; prepositional relative constructions and their chopping and resumptive counterparts; and the alternation between inflected and uninflected infinitival constructions.